Microstructure, electrical resistivity, and tensile properties of neutron-irradiated Cu–Cr–Nb–Zr - Perrin, Alice; Hamaguchi, Dai; Geringer, Josina W.; Zinkle, Steve; Yang, Ying; Skutnik, Steve; Poplawsky, Jon; Katoh, Yutai (Frontiers in Nuclear Engineering, 2024)
High strength, high conductivity copper alloys that can resist creep at high temperatures are one of the primary candidates for efficient heat exchangers in fusion reactors. Cu-Cr-Nb-Zr alloys, which were designed to improve the strength and creep life of the ITER Cu-Cr-Zr reference alloys, have been found to have comparable electrical conductivity and tensile properties of Cu-Cr-Zr alloysThe measured creep rupture times for these improved alloys is about ten times higher than the ITER reference alloys at 90-125 MPa at 500℃. However, the effects of neutron irradiation on these alloys, and the ensuing material properties, have not been studied, and thus their utility in a fusion reactor environment is not well understood. This work characterizes the room temperature mechanical and electrical properties of a neutron irradiated Cu-Cr-Nb-Zr alloy and compares them to neutron irradiated ITER reference heat sink Cu-Cr-Zr alloy. Tensile specimens were neutron irradiated in the High Flux Isotope Reactor (HFIR) to 5 dpa between 275℃ and 325℃. Post-irradiation characterization included electrical resistivity measurements, hardness, and tensile tests. Microstructural evaluation used scanning electron microscopy, energy dispersive x-ray spectroscopy, and atom probe tomography to characterize the irradiation-produced changes in the microstructure and investigate the mechanistic processes leading to the post-irradiation properties. Transmutation calculations were validated with composition measurements from atom probe data and used to calculate contributions to the increase in electrical resistivity measured after irradiation. Comparisons with Cu-Cr-Zr alloys in the same irradiation heat found that the post-irradiated Cu-Cr-Nb-Zr alloys and Cu-Cr-Zr alloys had comparable electrical resistivity. While Cu-Cr-Nb-Zr alloys suffered more irradiation hardening than Cu-Cr-Zr, the overall tensile behavior deviated very little from non-irradiated values in the studied temperature range.